The renin-angiotensin system mediates epidermal growth factor receptor-vitamin D receptor cross-talk in colitis-associated colon cancer - Dougherty, Urszula (Clin Cancer Res, 2014)
PURPOSE: We previously showed that epidermal growth factor receptor (EGFR) promotes tumorigenesis in the azoxymethane/dextran sulfate sodium (AOM/DSS) model, whereas vitamin D (VD) suppresses tumorigenesis. EGFR-vitamin D receptor (VDR) interactions, however, are incompletely understood. VD inhibits the renin-angiotensin system (RAS), whereas RAS can activate EGFR. We aimed to elucidate EGFR-VDR cross-talk in colorectal carcinogenesis. EXPERIMENTAL DESIGN: To examine VDR-RAS interactions, we treated Vdr+/+ and Vdr/− mice with AOM/DSS. Effects of VDR on RAS and EGFR were examined by Westerns, immunostaining and real time PCR. We also examined the effect of vitamin D3 on colonic RAS in Vdr+/+ mice. EGFR regulation of VDR was examined in hypomorphic Egfr(Waved2) (Wa2) and Egfr(wildtype) mice. Ang II-induced EGFR activation was studied in cell culture. RESULTS: Vdr deletion significantly increased tumorigenesis, activated EGFR and βcatenin signaling and increased colonic RAS components: including renin and angiotensin II. Dietary VD3 supplementation suppressed colonic renin. Renin was increased in human colon cancers. In studies in vitro, Ang II activated EGFR and stimulated colon cancer cell proliferation by an EGFR-mediated mechanism. Ang II also activated macrophages and colonic fibroblasts. Compared to tumors from Egfr(Waved2) mice, tumors from Egfr(wildtype) mice showed up-regulated Snail1, a suppressor of VDR, and down-regulated VDR. CONCLUSIONS: VDR suppresses the colonic RAS cascade, limits EGFR signals and inhibits colitis-associated tumorigenesis, whereas EGFR increases Snail1 and down-regulates VDR in colonic tumors. Taken together, these results uncover a RAS-dependent mechanism mediating EGFR and VDR cross-talk in colon cancer.